2008
DOI: 10.1093/ilar.49.3.277
|View full text |Cite
|
Sign up to set email alerts
|

Lurking in the Shadows: Emerging Rodent Infectious Diseases

Abstract: Rodent parvoviruses, Helicobacter spp., murine norovirus, and several other previously unknown infectious agents have emerged in laboratory rodents relatively recently. These agents have been discovered serendipitously or through active investigation of atypical serology results, cell culture contamination, unexpected histopathology, or previously unrecognized clinical disease syndromes. The potential research impact of these agents is not fully known. Infected rodents have demonstrated immunomodulation, tumor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
24
0
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(26 citation statements)
references
References 101 publications
1
24
0
1
Order By: Relevance
“…As discussed elsewhere, parvoviruses remain, both individually and as a group, among the most prevalent viruses in laboratory rats and mice (Besselsen et al 2008;Carty 2008;Clifford and Cosentino 2006a,b;Livingston and Riley 2003). In light of the significant biological similarities among rodent parvoviruses, we consider the reasons for their continued presence in general.…”
Section: Why They Persistmentioning
confidence: 93%
See 1 more Smart Citation
“…As discussed elsewhere, parvoviruses remain, both individually and as a group, among the most prevalent viruses in laboratory rats and mice (Besselsen et al 2008;Carty 2008;Clifford and Cosentino 2006a,b;Livingston and Riley 2003). In light of the significant biological similarities among rodent parvoviruses, we consider the reasons for their continued presence in general.…”
Section: Why They Persistmentioning
confidence: 93%
“…Research effects of parvovirus infection of rats and mice include well-demonstrated and long-lasting effects on the immune system, oncology studies, and lymphocyte cultures (Besselsen et al 2008;Ellerman et al 1996;Jacoby et al 1996;McKisic et al 1995). But despite the substantial literature of parvoviral interference with research, it is sometimes difficult to garner the necessary commitment from principal investigators.…”
Section: Effects On Researchmentioning
confidence: 99%
“…The strategies used to control or eliminate emerging and reemerging pathogens, as called outbreak response, especially opportunistic microorganisms from the laboratory animal colony depend on these organisms' risk to institutional programs (Besselsen et al, 2008). The strategies include consideration of the colony requirements, numbers of animals at risk, and available facility resources together with the selective control measures' cost, complexity, and probability of success (Hedin and Widerstrom, 1998).…”
Section: CMmentioning
confidence: 99%
“…The strategies include consideration of the colony requirements, numbers of animals at risk, and available facility resources together with the selective control measures' cost, complexity, and probability of success (Hedin and Widerstrom, 1998). The opportunistic pathogens were denoted an organism capable of causing disease only in a host whose resistance is lowered (Waggie et al, 1994;Hedin and Widerstrom, 1998;Besselsen et al, 2008). They do not affect research and breeding performance uniformly.…”
Section: CMmentioning
confidence: 99%
“…Despite stringent procedures, several emerging and re-emerging pathogens have been recently identified in rodent laboratory colonies, including the murine norovirus. 3,4 The threat represented by emerging pathogens led to the organization of a workshop dedicated to the 'Detection, Impact and Control of Specific Pathogens in Animal Resource Facilities' in 2009. One major conclusion of this workshop was the recommendation of 'the improvement of communications of disease outbreaks and potential risks for animal models for the scientific community'.…”
mentioning
confidence: 99%